1993
DOI: 10.1159/000284811
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Prediction of Treatment Efficacy and One-Year Outcome in Schizophrenia

Abstract: The present study was conducted to establish the degree of interrelationship between neuropsychological functioning in the acute phase of the schizophrenic illness, clinical measures of treatment response (positive and negative symptoms), and 1-year outcome. Nineteen SADS/RDC schizophrenic inpatients were clinically rated during a 2-week drug washout period and again following 4 weeks of neuroleptic treatment. The findings revealed that reduced attentional ability in the baseline phase significantly predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
8

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 7 publications
0
21
0
8
Order By: Relevance
“…Preliminary results show that psychomotor speed has more predictive value for functional outcome as has been highlighted in recent overviews . A number of earlier studies have indeed indicated that psychomotor measures have predictive value for the long-term daily living situation of patients with schizophrenia after release from a psychiatric hospital (Weaver & Brooks, 1967;Buchanan et al, 1994;Goldman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results show that psychomotor speed has more predictive value for functional outcome as has been highlighted in recent overviews . A number of earlier studies have indeed indicated that psychomotor measures have predictive value for the long-term daily living situation of patients with schizophrenia after release from a psychiatric hospital (Weaver & Brooks, 1967;Buchanan et al, 1994;Goldman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…First, in a recent review, Fenton et al [17] hypothesized that poor medication compliance in a subgroup of patients may result from forgetting to take prescribed medication which may lead to increased psychopathology. Secondly, memory impairments are the most remarkable cognitive predictor of functional outcome [18]. In his review on the functional consequences of neurocognitive deficits Green [5] writes: 'Not one of the seven studies that included measures of secondary verbal memory failed to show an association regardless of the functional outcome measures'.…”
Section: Discussionmentioning
confidence: 99%
“…Se obtienen importantes correlaciones entre el déficit neuropsicológico y el curso de la esquizofrenia (31,32,33), en el sentido que en pacientes con mayor déficit cognitivo se detecta un peor curso del trastorno.…”
Section: Curso De La Esquizofreniaunclassified